CORRELATION OF VISUAL FIELD LOSS TO ACTIVITIES OF DAILY LIVING DISTURBANCE ON GLAUCOMA OUTPATIENTS IN SURABAYA - Pryandhini, Pradistya Astri; Primitasari, Yulia; Setiawati, Yunias; Komaratih, Evelyn (The Indonesian Journal of Public Health, 2025)
Introduction: Glaucoma is known as a thief of sight due to its progressive visual field loss with symptoms typically manifesting only at advanced stages. Visual field loss, particularly peripheral vision, can affect patients’ quality of life (QoL) in performing activities of daily living. Glaucoma cases are predicted to rise by 74% worldwide between 2013 and 2040. Aims: Assess the correlation between the degree of visual field loss and disturbance in activities of daily living in glaucoma outpatients. Methods: A total of 60 patients from Dr. Soetomo General Academic Hospital were interviewed using the NEI VFQ-25 on near vision, distance vision, peripheral vision, social function, driving, and dependency subscales. Visual field loss was assessed using the Humphrey Visual Field Analyzer (HFA) and categorized based on the Hodapp, Parish, and Anderson (HPA) classification using the better-eye mean deviation value. Meanwhile, Spearman’s rank correlation was used to determine the correlation between the patients’ visual field loss and NEI VFQ-25 interview results. Results: Significant moderate correlations were observed between visual field loss and the social function (r = 0.545) and dependency (r = 0.483) subscales. Significant weak correlations were observed in the near vision (r = 0.351), distance vision (r = 0.383), and peripheral vision (r = 0.398) subscales. An insignificant weak correlation was observed in the driving subscale (r = 0.262). Conclusion: Visual field loss in glaucoma patients is associated with impaired performance in activities of daily living, with the severity of limitation increasing in line with the progression of visual field loss.